Genomic characterization of Salmonella enterica isolates causing typhoid among Ghanaian patients - Emmanuel K. Sam; Derrick A. Daah; Doreen Akorwome; Righteous K. Agoha; Enock K. Amoako; Collins M. Morang′a; Lucas N. Amenga-Etego; Samuel Duodu (PLoS ONE, 2026)
Salmonella enterica serovar Typhi ( S . Typhi) is a leading cause of typhoid fever, significantly impacting morbidity and mortality in Ghana. However, genome-resolved data on circulating typhoidal strains remains scarce. We conducted this study to explore the genetic diversity, virulence, and antimicrobial resistance (AMR) profiles of S . enterica strains isolated from clinically diagnosed typhoid patients to inform targeted management and surveillance strategies. Twenty-eight S . enterica isolates recovered from stool and blood cultures were confirmed by PCR targeting 211 bp amplicon of the bcfD gene. Whole-genome sequencing was performed on all isolates followed by multi-locus sequence typing (MLST), SPIFinder, ResFinder, and phylogenetic analyses to characterize sequence types (STs), virulence markers, including antibiotic resistance genes and to define clonal relatedness. The GenoTyphi program was used to assign isolates within known S . Typhi lineages. For regional comparison, publicly available S . enterica genomes and their corresponding metadata were retrieved from the Bacterial and Viral Bioinformatics Resource Center (BV-BRC) and Pathogenwatch and included in the phylogenetic analysis. MLST revealed significant genetic diversity, with S . Typhi ST02 and S . Typhimurium ST19 and ST313 being notable. ST02 isolates, predominantly linked to typhoidal strains, formed distinct clusters with isolates from neighboring West African countries, indicating regional transmission dynamics. ST313, associated with invasive infections, was isolated from stool samples. The study identified a high prevalence of virulence genes such as invA , invE , sopB , sopD , cdtB , pltA , and pltB among STs that are not implicated in typhoidal salmonellosis. Plasmid analysis showed limited diversity, with plasmid replicons detected in only a subset of isolates (n = 12/28, 42.9%). Plasmid carriage was universal in S. Typhimurium (4/4, 100%), dominated by IncFIB(S) and IncFII(S), with IncQ1 also detected in two isolates. In contrast, plasmids were rare in S. Typhi (1/6, 16.7%), where only a single isolate harbored IncFIB(S) and IncFII(S). Other non-typhoidal serovars (n = 18) showed moderate carriage (7/18, 38.9%) and greater plasmid diversity. In addition to IncF-type replicons, these isolates harbored Col(pHAD28), IncN, and IncFIB(K). Antibiotic resistance genes were detected at low frequencies, including bla TEM variants (beta-lactam resistance, n = 3), qnr (quinolone resistance, n = 3), sul1 / sul2 (sulfonamide resistance, n = 3), aadA1 , aph(6)-Id , aac(3)-IIa (aminoglycoside-modifying enzymes, n = 3) , tet(A ) (tetracycline resistance, n = 2), dfrA1 (trimethoprim resistance, n = 1), and catA1 (chloramphenicol resistance, n = 1), highlighting limited antimicrobial resistance potential in the populations sampled. The serovars identified were S . Typhi (n = 6), S . Infantis (n = 4), S . Virchow (n = 4), S . Chester (n = 2), S . Jukestown (n = 1), S . Durham (n = 4), S . Typhimurium (n = 4), S . Wein (n = 1), S . Bangui (n = 1) and S . Saintpaul (n = 1). Phylogenetic analysis positioned the isolates recovered from the current study within clades of other regional isolates with global clinical relevance. The S . Typhi isolates belonged to lineage 3.2.1, not previously reported in Ghana, and not typically associated with multidrug resistance. This study provides an important insight into the genetic characteristics of S . enterica strains associated with typhoid fever among Ghanaian patients. Several non-typhoidal Salmonella (NTS) strains were found to harbor virulence determinants, including toxin-associated genes implicated in typhoid pathogenesis, highlighting their potential clinical relevance.